Analisis Nilai-nilai Pendidikan Karakter dalam Novel “Love For Show” Karya Andi Eriawan - Dernius Hura (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Novel is one of the literary works written by the author based on himself or other people's experiences. Novels are liked by many people because there are moral values ​​that are useful for everyday life. These moral values ​​relate to character education which has always been considered important for social life. Character education is often considered trivial because the delivery is not as clear as the delivery of formal education. In the novel "Love For Show" by Andi Eriawan contains many character education values ​​that can change the behavior of the reader for the better. This study aims to describe the values ​​of character education in the novel "Love For Show" by Andi Eriawan. The method used is descriptive qualitative. The object of research is the novel "Love For Show" by Andi Eriawan. The data collection technique is by searching for data in the form of novels, the second stage is reading carefully every line of the novel, the third stage is collecting data by searching for and marking passages that contain character values, the fourth stage is coding the novel fragments that contain character values , the fifth stage of classifying and describing the novel's character values, the sixth stage by concluding the results of the analysis of the character values ​​in the novel. Data analysis was carried out by researchers, namely content analysis. Drawing conclusions using deductive and inductive. The results of this study indicate eight character education values ​​contained in the novel "Love For Show" by Andi Eriawan, namely (1) religious values, (2) honest values, (3) hard work values, (4) creative values, ( 5) the value of friendship, (6) the value of loving peace, (7) the value of liking to read, and (8) responsibility.